2008
DOI: 10.1209/0295-5075/83/24002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic lift of vesicles under shear flow in microgravity

Abstract: The dynamics of a vesicle suspension in a shear flow between parallel plates has been investigated under microgravity conditions, where vesicles are only submitted to hydrodynamic effects such as lift forces due to the presence of walls and drag forces. The temporal evolution of the spatial distribution of the vesicles has been recorded thanks to digital holographic microscopy, during parabolic flights and under normal gravity conditions. The collected data demonstrates that vesicles are pushed away from the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 26 publications
(61 reference statements)
11
50
0
Order By: Relevance
“…When they are sheared close to a wall, a lift force of viscous origin appears which pushes vesicles away from the wall. This lift force is a consequence of the fore-aft asymmetry of the flow between the deformable vesicle and the wall : the pressure distribution due to the contraction and expansion of the flow is asymmetric (contrary to what would happen with a rigid sphere near a wall) and results in a net force (Olla 1997;Cantat and Misbah 1999;Callens et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When they are sheared close to a wall, a lift force of viscous origin appears which pushes vesicles away from the wall. This lift force is a consequence of the fore-aft asymmetry of the flow between the deformable vesicle and the wall : the pressure distribution due to the contraction and expansion of the flow is asymmetric (contrary to what would happen with a rigid sphere near a wall) and results in a net force (Olla 1997;Cantat and Misbah 1999;Callens et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] In agreement with the numerical and theoretical studies for simple shear flows, 22,24 we showed recently that the migration velocity decreases like 1 / y 2 , where y is the distance to the wall of the center of mass of the vesicle. 26 ͑ii͒ The nonconstant shear rate in a parabolic velocity profile ͑even unbounded͒ leads to a subtle interplay between the gradient of shear and the shape, 27 resulting in migration toward the center with a constant drift velocity except near the centerline. In a realistic channel, both effects coexist and we shall see that this leads to a new and nontrivial noninertial migration law.…”
mentioning
confidence: 99%
“…Due to the lift force from a wall [25][26][27] and the migration in a parabolic Poiseuille flow [28,29], vesicles are aligned close to the center of the channel. In the glucose solutions, the buoyancy force leads to a displacement of the vesicles from the center of the channel in the z-direction (see Fig.…”
mentioning
confidence: 99%